Führung und Arbeitsbedingungen in der digitalisierten öffentlichen Verwaltung - Dreas, Susanne A. (Modernisierung des öffentlichen Sektors ("Gelbe Reihe"), 2021)
Employee participation and co-management are critical success factors for the digital transformation of public administration. By evaluating the development and implementation of digital innovations in the field of HRM, leadership, communication and organisational design in seven German public-sector organisations, this study identifies barriers and facilitators in the digital transformation of the public sector. It reflects on how to create decent work in the digital age and presents recommendations for HR managers, policymakers, staff councils and labour unions.